Biomechanical Comparison of Double 2.3-mm Headless Cannulated Self-Compression Screws and Single 3.5-mm Cortical Screw in Lag Fashion in a Canine Sacroiliac Luxation Model: A Small Dog Cadaveric Study - Kang, AhRan; Lee, Haebeom; Lee, Arim; Roh, Yoonho; Sim, Bokyun; Jeong, Jaemin (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to evaluate the feasibility of safe positioning of double 2.3-mm headless cannulated self-compression screws (HCS) in a small dog cadaveric sacroiliac luxation model and to compare the static rotational biomechanical properties of fixation repaired using two different screw systems with a minimally invasive osteosynthesis technique: double 2.3-mm HCS and a single 3.5-mm standard cortical screw placed in a lag fashion.Study Design A unilateral small dog sacroiliac luxation model was stabilized using double 2.3-mm HCS (n = 11) or a single 3.5-mm cortical screw (n = 11). Radiographic and computed tomography (CT) imaging analyses and biomechanical testing of rotational force on the sacroiliac joint of both fixations were performed. The maximum load at failure and failure modes of each fixation were recorded and compared.Results Fluoroscopically guided percutaneous application of double HCS was safe in a unilateral sacroiliac luxation model in small dogs without violation of the vertebral and ventral sacral foramen. Furthermore, resistance to rotational force applied on fixation of the sacroiliac joint repaired with double 2.3-mm HCS estimated by maximum failure load was significantly higher than that of a single 3.5-mm cortical screw (p < 0.001).Conclusion Although this was an experimental cadaveric study, based on our results, the use of smaller double HCS may be beneficial as an alternative to the conventional single lag screw for stabilization of sacroiliac luxation in small dogs.
Keywords: sacroiliac luxation; headless cannulated self-compression screw; lag screw; biomechanical study; dog